ANALISIS AKUNTANSI LINGKUNGAN PADA PENGELOLAAN LIMBAH SEBAGAI SALAH SATU BENTUK TANGGUNG JAWAB CSR SOSIAL PADA PERUSAHAAN PT SUGAR GROUP COMPANIES - Sri Yanti; Nedi Hendri; Jawoto Nusantoro (Jurnal Akuntansi AKTIVA, 2021)
This study aims to determine environmental accounting for waste management as a form of social CSR responsibility in PT Sugar Group Companies. This type of research is descriptive research. Data analysis of Miles and Huberman's model, namely data reduction, data display, and conclusion drawing / verification. The results of this study indicate that the application of environmental accounting to waste management at PT Sugar Group Companies has been carried out well. However, environmental costs are not measured in detail, such as the cost of implementing labor and the cost of water and electricity which are totaled in terms of production activities. PT Sugar Group Companies have run a CSR program better known as PKBL (Partnership and Community Development Program), PKBL is carried out in a series of planned and measured activities.